Pemanfaatan Batu Megalitikum di Mandrehe Nias Barat sebagai Sumber Belajar Sejarah - Arnifelis Gulo; Saiful Anwar Matondang; Pulung Sumantri (Medan Resource Center, 2022)
The objectives of this study are : to examine the use of megalithic stones as a source of historical learning in Mandrehe Sub-Distric. Megalithic stone is etymologically, megalithic come from the word whict means big, and lithos whict means stone. Therefore, the megalithic are is commonly referred to as the big stone age. History learning resources are all sources (whether in the from of data, people or objects) that can be utilized or can be used to provide facilities (convenience) for learning for students. Learning resources can be used to make a positive contribution to improving the quality of education and learning. History is a science the is compiled on the results of the investigation of several events that can be proven by the material facts. To reveal the problem of this research, secondary data and primary data were used by using observation, interview, and questionnaire techniques. This study aims to determine the historicity of megalith sites in Mandrehe Sub-District. The results of the study show that the role of the government is very important to support the use of megalith sites as history learning resources. If the existing megalith site can be maintained properly, it can be utilized in various ways, one of whichis a field trip and learning resources.